Penerapan Model Pembelajaran Problem Based Learning dalam Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran PPKn Kelas XI IPA 7 UPT SMA Negeri 2 Parepare - kartika, reztu dwi (Makassar Journal of Social Sciences, 2023)
This study aims to improve student learning outcomes in Civics subjects material Threats to National Integration through the Problem Based Learning learning model for class XI IPA 7 UPT SMA Negeri 2 Parepare. This research has stages of research in the form of cycles. The cycle in this study was carried out in 2 cycles, Cycle I and Cycle II. The subjects of this study were 34 students of class XI IPA 7 UPT SMA Negeri 2 Parepare. The data collection methods used were written tests, observation sheets, and documentation.The results of the research in Cycle I and Cycle II obtained the following data: before using the Problem-Based Learning Model in Civics learning at the initial stage test scores obtained 4 students (11.76%) who completed and 30 students (88.23%) who did not complete their studies. After giving teaching actions using the Problem Based Learning Learning Model, in the first cycle the learning mastery increased by 15 students or 44.11% of students completed. After conducting research from cycle I to cycle II, cycle II obtained increased mastery, there were 29 students or 85.29% complete and as many as 5 students or 14.07% who had not achieved completeness. This shows that the use of the Problem Based Learning Learning Model can improve the learning outcomes of Threats to National Integration material in class XI IPA 7 UPT SMA Negeri 2 Parepare.